Understanding user acceptance of blockchain-based smart locker. Issue 2 (31st January 2020) - Lian, Jiunn-Woei; Chen, Chih-Teng; Shen, Li-Fang; Chen, Hung-Ming
Abstract : Purpose: The purpose of this study is to explore the critical factors that affect users' acceptance and usage intention toward blockchain-based smart lockers. Design/methodology/approach: The research is designed in two phases. In the first phase, the key stakeholders are interviewed. Participants include managers from technology providers and logistics companies. In the second phase, a questionnaire survey is used to validate the proposed model. Findings: Based on the final results, this study makes the following three suggestions. First, perceived usefulness and perceived ease of use are the critical factors. In other words, it is important to emphasize the function and convenience of a new service when introducing it to a potential user. Second, safety is not the major concern when using a blockchain-based smart locker. This means that users will trust the service provider for providing a secure service. Users do not worry about the security problem. Finally, the network externality of smart locker is also insignificant. Originality/value: This study has three major contributions. First, this study identifies the critical factors that will affect user acceptance of blockchain-based smart lockers. Next, this study combines the opinions from service providers and users to understand the gap between different stakeholders. Finally, this study can enrich our understanding on the applications of blockchain from a managerial perspective and not only from a technical perspective, as in most previous studies.